ANALYSE DU NIVEAU D’IMPLICATION DE LA POPULATION LOCALE DANS LA DELIMITATION DUPARC NATIONAL DE LA LOMAMI /PROVINCE DU MAMIEMA (RDC) - UYULU, Johnson YAMBA (IJRDO - Journal of Social Science and Humanities Research, 2019)
This experience on the level analysis of the involvement of the population in the ranking process is not questioned today. However the durability of the lomami National Park with its exceptional flora and fauna as well as the valorization Its scientific and economic resources can only be fully realized in a context of collaboration between state services and the local population. Thus 62% of the respondents were involved in the delimitation process of the lomami national park during group meetings, individual interviews. More than 90% of those interviewed have already heard about the creation of the Park, 29% of whom are agents of the state, 29% have heard through the channel of people associated with conservation organizations, 23% through radio and 13 % from another member of the community.